Power and legitimacy reconciling Europe and the nation-state - Lindseth, Peter L. (New York ; Oxford : Oxford University Press, 2011)
The implications of European integration for national democracy and constitutionalism are well known. Nevertheless, as the events of the last decade made clear, the EU's complex system of governance has been unable to achieve a democratic or constitutional legitimacy in its own right. The author traces the roots of this paradox.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Administrative law -- European Union countries; International and municipal law -- European Union countries; Legitimacy of governments -- European Union countries